Impact of partcipatory forest management on the livelihoods of indigenous communities - Neethu Mary Newton; Gopakumar, S (Guide) (Vellanikkara Department of Natural Resource Management College of Forestry, 2019)
The present study (3z(BImpact of participatory forest management on livelihoods of indigenous communities(3y (Bwas conducted in five randomly selected VSS which were active in Central Forest Circle, Thrissur. The objectives of the study were to understand the impact of participatory forest management on livelihoods of indigenous communities. A perception analysis to know the pre-PFM and post-PFM situations as perceived by the community was also done. Sustainable livelihood analysis was the method used for the impact study. Primary data was collected through a pre-tested interview schedule. Secondary data was collected from forest department records, village records and from discussion with people. The study revealed that PFM had a positive impact on the livelihood of the local communities in the selected five Vana Samrakshana Samithies namely Anapantham VSS, Karikadavu VSS, Kunchipara VSS, Poovanchira VSS and Vazhachal VSS. Impact analysis of Anapantham VSS showed that after the implementation of PFM activities, there were improvements in the financial capital, physical capital and social capital while a reduction was noticed in the natural capital and human capital compared to the pre-PFM situation. Impact analysis of Karikadavu VSS showed that after the implementation of PFM activities, there were improvements in the social capital, financial capital and physical capital. At the same time, a reduction was noticed in the natural capital and human capital compared to the pre-PFM situation. Impact analysis of Kunchipara VSS showed that after the implementation of PFM activities, there were improvements in the physical capital, financial capital and social capital. On the other hand, the human capital was unaffected. At the same time, a reduction was noticed in the natural capital compared to the pre-PFM situation. Impact analysis of Poovanchira VSS showed that after the implementation of PFM activities, there were improvements in the financial capital, physical capital, human capital and social capital. At the same time, a reduction was noticed in the natural capital compared to the pre-PFM situation. Impact analysis of Vazhachal VSS showed that after the implementation of PFM activities, there were improvements in the financial capital, physical capital and social capital. At the same time, a reduction was noticed in the natural capital and human capital compared to the pre-PFM situation. Perceptions of local people regarding the conditions before and after PFM were different in all the VSS. The difference in perception was highest in Poovanchira VSS, while the lowest variation was observed in Kunchipara VSS and Karikadavu VSS. The highest variation in perception score was in Vazhachal VSS and the lowest variation in perception score was in Poovanchira VSS. PFM activities were not significantly different in the three pairs of VSS namely Anapantham & Karikadavu, Vazhachal & Anapantham and Vazhachal & Karikadavu before implementation of PFM. PFM activities were not significantly different in four pairs of VSS namely Anapantham & Karikadavu, Anapantham & Kunchipara, Kunchipara & Karikadavu and Poovanchira & Kunchipara was observed. Suggestions to improve the underperforming capitals in the various VSS include increase in number of work days, planting of trees, restrictions on waste disposal in the water bodies.s
MSc
Keywords: Forestry